Penilaian Produk Atau Hasil Kerja Peserta Didik: Kajian Pustaka Teknik, Tahapan, dan Penerapannya dalam Pembelajaran - Angga Septi Nur Wicaksono; Avtyo Laura Ananda; Reza Dwi Kurniarti (Prosiding Konferensi Ilmiah Dasar, 2026)
Product assessment is an authentic assessment technique that measures both the process and the final quality of the work produced by learners, going beyond what a written test alone can capture. This article presents a conceptual review of product assessment, drawing on a library-based synthesis of textbooks and recent journal articles. The discussion covers the meaning of product assessment, its three developmental stages (preparation, production, and appraisal), its purposes, its two scoring techniques (holistic and analytic), and its advantages and limitations. An illustrative application in a science lesson on the water cycle is presented, including a scoring rubric and the scoring formula used to convert raw scores into a final grade. The review shows that product assessment gives a more complete picture of learners' cognitive, psychomotor, and affective competencies than conventional testing, and is increasingly relevant under competency-based curricula, although it demands more time, clearer rubrics, and adequate facilities to be implemented effectively.